Design and Construction of Miniature Biogas Power Plant in Balahu Village by Utilizing Cow Livestock Waste - Asri, Muhammad; Hulukati, Stephan Adriansyah (Graduate School, Universitas Brawijaya, 2023)
Indonesia is a country with the largest palm oil industry in the world. Palm oil mill effluent is oily and non-toxic liquid waste, the result of palm oil processing. Although non-toxic, the effluent can cause environmental disasters because it is dumped in open ponds and releases large amounts of methane gas and other harmful gases that cause greenhouse gas emissions. This research was conducted with experimental research methods. The purpose of this study, namely to obtain an explanation of the problem studied in the explanation in the form of a causal relationship between the dependent variable and the independent variable that affects the occurrence of the problem. In the biogas turbine section, it is made by adjusting the working principle of water turbines in general. The biogas storage section uses an existing biogas system and then the gas is channeled through a inch pipe. After that the gas flows so that it rotates the turbine and the turbine rotates then produces electricity and is accommodated in a 12 Volt battery so that it can be used at night without having to turn on the turbine. stored on the battery when the battery is full will be turned off by the control system in the device design so that it is effective and efficient.